An Examination Of Residents’ Attitudes Toward Tourism Development: The Case Of Aqaba In Jordan - Al-Badarneh, Mohammad Bader Helal (2014)
Generally, the economic contribution of tourism is the most highly researched field in terms of tourism impacts on host communities. Nevertheless, social and cultural changes in host communities should have equal attentions by scholars and official planners when designing tourism policies and strategies. To measure how community members perceive tourism impacts, theoretical foundations and a set of predictors were used. Social exchange was one of the first social theories that have been used for this purpose. Based on the contradictory results in many previous studies that used this theory, it was found that using a single theory does not lead to meaningful findings. Accordingly, the current study is an attempt to develop a new model based on Perdue et al’s (1990) model. This theoretical model consists of social exchange theory (SET) and power theory. Six main hypotheses were tested to point out the relationship between the independent variables (a set of predictor factors, power, and SET) and the dependent variable (residents’ support for tourism). The moderation relationship of power and SET was also examined in order to explain this relationship in other conditions; this is a way to explain possible contradictory results concerning the relationships between predictor factors and attitudes. Based on the quantitative results, significant relationships were found between all the independent variables and support for tourism.